Kajian Mekanisme Estrogenik Kombinasi Ekstrak Kemangi dan Adas melalui Histopat Ovarium dan Uterus - Yulianita Yulianita; E. Mulyati Effendi; Triastinurmiatiningsih Triastinurmiatiningsih (Fakultas Farmasi Universitas Pancasila, 2020)
Research on the Estrogenic Mechanism Study of the Combination of Basil Herb (Ocimumamericanum) and Fennel Fruit (Foeniculum vulgare) against the background of research results whichshowed that the combination of 70% ethanol extract of basil herbs 0.35g / 200g BB and fennel fruit0.0725g / 200g BB had effi cacy estrogenic because it greatly aff ects the duration of the estrus phase,vascularization and weight of the ovaries and uterus. The aim and target to be achieved from thisresearch is to know the working mechanism of the combination of estrogenic basil and fennel fruitherbs. The parameters observed were histopathological examination of the ovary and uterus. Histopathictest results in the ovary and uterus show the eff ect of treatment on the development of follicles in theovary and uterine wall thickening. So it can be concluded that the mechanism of estrogenic combinationof basil and fennel fruit extracts occurs through the mechanism of genomics, where phytoestrogencompounds in both plants pass through cell membranes and interact with receptors so that they canproduce estrogen-like eff ects.